Interactions of the Skin Pathogen Haemophilus ducreyi With the Human Host - Brothwell, Julie A.; Griesenauer, Brad; Chen, Li; Spinola, Stanley M. (Frontiers in Immunology, 2021)
The obligate human pathogen Haemophilus ducreyi causes both cutaneous ulcers in children and sexually transmitted genital ulcers (chancroid) in adults. Pathogenesis is dependent on avoiding phagocytosis and exploiting the suppurative granuloma-like niche, which contains a myriad of innate immune cells and memory T cells. Despite this immune infiltrate, long-lived immune protection does not develop against repeated H. ducreyi infections—even with the same strain. Most of what we know about infectious skin diseases comes from naturally occurring infections and/or animal models; however, for H. ducreyi, this information comes from an experimental model of infection in human volunteers that was developed nearly three decades ago. The model mirrors the progression of natural disease and serves as a valuable tool to determine the composition of the immune cell infiltrate early in disease and to identify host and bacterial factors that are required for the establishment of infection and disease progression. Most recently, holistic investigation of the experimentally infected skin microenvironment using multiple “omics” techniques has revealed that non-canonical bacterial virulence factors, such as genes involved in central metabolism, may be relevant to disease progression. Thus, the immune system not only defends the host against H. ducreyi, but also dictates the nutrient availability for the invading bacteria, which must adapt their gene expression to exploit the inflammatory metabolic niche. These findings have broadened our view of the host-pathogen interaction network from considering only classical, effector-based virulence paradigms to include adaptations to the metabolic environment. How both host and bacterial factors interact to determine infection outcome is a current focus in the field. Here, we review what we have learned from experimental H. ducreyi infection about host-pathogen interactions, make comparisons to what is known for other skin pathogens, and discuss how novel technologies will deepen our understanding of this infection.